TEACHER COMPETENCE AND DIFFICULTIES IN CONSTRUCTING HOTS INSTRUMENTS IN ECONOMICS SUBJECT - Dadang Dahlan; Leni Permana; Mutiya Oktariani (LPMPP Universitas Negeri Yogyakarta, 2020)
This research was motivated by the students’ low high order thinking skill which was related to teachers’ low competence in constructing high order thinking skills instrument. This study was intended to describe economics teachers’ competence and difficulties in developing instruments to measure higher order thinking skills. The subjects of this study were 45 economics teachers and 270 students from 27 public high schools in Bandung. The study employed quantitative survey method with questionnaire and focus group discussion (FGD) as the instruments. The survey method was carried out to describe the teachers’ competences and difficulties in constructing instruments. The results of the study indicated that the teacher's competence in constructing high order thinking skills instruments was low. The research findings showed that only 12% of the teacher-made questions can be categorized at the analyzing level to creating level, and 88% were categorized in remembering to applying level. This resulted in the teachers’ obstacles in constructing higher order thinking skills instruments. The research findings signified that 80% of the teachers faced difficulties in constructing essay and multiple choices instruments.